Comparison of Risk Factors and Outcomes in Pediatric Posterior and Anterior Circulation Arterial Ischemic Stroke: A Cross-Sectional Analysis - Jahanshahi, Amirreza; Niknam, Mahsa; Raeisi, Sina; Sadeghvand, Shahram; Mahmoudi Azar, Sepehr; Ghassemi, Atiyeh; rezazadeh, khatereh (Iranian Journal of Child Neurology, 2025)
Objectives: Pediatric arterial ischemic stroke (AIS) is a rare but serious condition leading to significant neurological disability. AIS is classified into anterior circulation AIS (ACAIS) and posterior circulation AIS (PCAIS). Understanding the differences between these subtypes is essential for early diagnosis and effective management. This study aimed to evaluate the demographic, clinical, and laboratory characteristics of pediatric ACAIS and PCAIS, focusing on lipid profiles, prothrombotic factors, and SARS-CoV-2 prevalence. Materials & Methods: A descriptive-analytical cross-sectional study was conducted on 34 children diagnosed with AIS at the Tabriz Children’s Hospital from March 2020 to October 2021. Patients were categorized into ACAIS, PCAIS, and mixed, involving both anterior and posterior circulations based on neuroimaging findings. Demographic data, medical history, and laboratory parameters, including coagulation factors, lipid profiles, and SARS-CoV-2 antibodies, were analyzed. Statistical comparisons were performed using SPSS version 26, with a p-value of <0.05 considered statistically significant. Results: Among the 34 patients, 73.5% were diagnosed with ACAIS, 20.6% with PCAIS, and 5.9% with both. PCAIS patients were older (median age: 8.0 vs. 2.0 years), and sex distribution varied, although not significantly. No significant differences were found in lipid profiles, coagulation factors, or SARS-CoV-2 prevalence between ACAIS and PCAIS groups. Conclusion: No significant differences in demographic features, lipid profiles, or prothrombotic conditions were observed between ACAIS and PCAIS, suggesting that pediatric stroke mechanisms may differ from those in adults. Further large-scale studies are warranted to validate these findings and improve pediatric stroke management.